Analisis Tingkat Kepadatan Vektor dan Binatang Pembawa Penyakit di RSI Surabaya Jemursari Tahun 2025 - Cahyaning, Nimas Elok; Suryono, Hadi; Rustanti, Iva; Hermiyanti, Pratiwi; Setiyadi, Fadjar (Sulolipu: Media Komunikasi Sivitas Akademika dan Masyarakat, 2025)
In hospitals, vector and disease-carrying animal control is very important because interaction between healthy and sick patients increases the risk of disease transmission. A preliminary study at RSI Jemursari showed that several types of vectors and disease-carrying animals were still found, along with several complaints related to their presence. This study aims to analyze the density of vectors and disease-carrying animals in hospitals. This study is a descriptive study with a cross-sectional approach over a specific period. The sample in this study includes mosquitoes, flies, cockroaches, and rats in inpatient areas with complaints, nutrition facilities, domestic waste and hazardous waste (B3) disposal sites, gardens, and canteens/cafés. Data were collected through observation, measurement, and interviews with pest control and sanitation staff at the hospital, then analyzed descriptively. The results showed that the fly population index in the nutrition unit, hazardous waste disposal site, and cafeteria/café met the criteria, but the domestic waste disposal site did not meet the criteria. Mosquito density based on habitat population index and container index met the criteria, but larvae were still found in the landfill outside the hospital building. The cockroach population index met the criteria, while rat density based on success traps did not meet the criteria. Overall, the control strategy at RSI Jemursari is in the good category, but it needs to be strengthened with monitoring of the environment outside the building, optimization of drainage, improvement of sanitation in storage areas, and environment-based vector control to create a healthier environment for patients, medical and non-medical staff, and hospital visitors.